2014
DOI: 10.1186/1746-1596-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Expression of serum amyloid A in uterine cervical cancer

Abstract: BackgroundAs an acute-phase protein, serum amyloid A (SAA) is expressed primarily in the liver. However, its expression in extrahepatic tissues, especially in tumor tissues, was also demonstrated recently. In our study, we investigated the expression of SAA in uterine cervical carcinomas, and our results suggested its potential as a serum biomarker.MethodsQuantitative real-time polymerase chain reaction (RT-PCR), immunohistochemistry (IHC) and enzyme-linked immunosorbent assay (ELISA) were used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
1
29
0
3
Order By: Relevance
“…Recent studies reported that cancer tissue might be a major source of SAA outside of the liver, such as in the patients with esophagus, lung, pancreas, ovary, uterine endometrium or uterine cervical cancer [1722]. In this study, we showed the presence of SAA protein in both tumor cells and macrophages in human breast carcinomas, and significantly more frequent expression of SAA mRNA in macrophages than tumor cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Recent studies reported that cancer tissue might be a major source of SAA outside of the liver, such as in the patients with esophagus, lung, pancreas, ovary, uterine endometrium or uterine cervical cancer [1722]. In this study, we showed the presence of SAA protein in both tumor cells and macrophages in human breast carcinomas, and significantly more frequent expression of SAA mRNA in macrophages than tumor cells.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, overexpression of SAA protein in tumor cells may reflect a high level of SAA protein secreted by the TAM in tumor microenvironment of breast cancer. In contrast, many researchers studied the local SAA genes' expression by RT-PCR analysis on RNA extracted from cancer biopsy specimens and speculated that the tumor cells are the main secretion source of SAA in local tumor tissues [21, 22]. One limitation of this method, unless combining tissue microdissection technique, is its inability to identify the location and secretion source in the complex cell components in tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,27,28,30 Lungs and lymph nodes are the most involved sites with distant metastasis from primary CNS tumors suggesting hematogenous and lymphogeneous pathways of dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…However, in event of a surgery, these conditions may be violated, increasing risk of metastasis. 17,31 …”
Section: Discussionmentioning
confidence: 99%